Digital Readiness Amidst Rural Realities: A Phenomenological Inquiry into Papuan Pre-service Teachers’ Experiences - Dewi Zulaiha (Academica: Journal of Multidisciplinary Studies, 2025)
The digital transformation of Indonesian education faces severe geographical and infrastructural hurdles, particularly within the Papua region, where a persistent digital divide complicates the implementation of modern educational standards. This phenomenological study explores how 26 Papuan pre-service teachers navigate the demands of the digital age alongside the mandates of the Kurikulum Merdeka (Independent Curriculum). Utilizing a qualitative approach, the research analyzes data collected from students across various districts in Biak to reveal the lived experiences of future educators in underdeveloped areas. The findings highlight a sharp contrast between professional idealism and structural reality; while these pre-service teachers demonstrate high levels of resilience by prioritizing "offline-first" pedagogy and the integration of local wisdom, their readiness is severely constrained by a lack of stable internet access, electricity, and essential digital devices. Furthermore, professional development is significantly hindered by limited access to training and workshops in these remote locations. This study concludes that the readiness of pre-service teachers is structurally limited rather than a result of personal capability. Consequently, the findings contribute to the field by emphasizing that policy interventions must shift from mere curriculum updates to prioritizing foundational infrastructure and localized training. Such targeted efforts are essential to ensure equitable educational progress and to bridge the gap between national digital expectations and the reality of rural Papuan classrooms.